2005
DOI: 10.1093/eurheartj/ehi259
|View full text |Cite
|
Sign up to set email alerts
|

The reproducibility and sensitivity of the 6-min walk test in elderly patients with chronic heart failure

Abstract: In elderly patients with CHF, the 6-MWT shows satisfactory agreement when repeated 1 year later. Change in 6-MWT distance is sensitive to change in self-perceived symptoms of heart failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
67
0
3

Year Published

2006
2006
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 111 publications
(71 citation statements)
references
References 46 publications
1
67
0
3
Order By: Relevance
“…Ingle et al (32) demonstrated its satisfactory reproducibility when repeated in the followup; they also showed that changes in distance walked after 1 year correlated well with the modification in self-perceived symptoms. However, they collected no information on the cognitive level of their large study cohort, and therefore the influence of cognitive function on the reliability and validity of this test was not determined.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Ingle et al (32) demonstrated its satisfactory reproducibility when repeated in the followup; they also showed that changes in distance walked after 1 year correlated well with the modification in self-perceived symptoms. However, they collected no information on the cognitive level of their large study cohort, and therefore the influence of cognitive function on the reliability and validity of this test was not determined.…”
Section: Discussionmentioning
confidence: 95%
“…However, they collected no information on the cognitive level of their large study cohort, and therefore the influence of cognitive function on the reliability and validity of this test was not determined. In addition, the authors acknowledged the lack of measures of anxiety or depression as a study limitation, proposing that alterations in psychological and behavior profiles could affect the reliability of the test (32).…”
Section: Discussionmentioning
confidence: 99%
“…6) In clinical cardiology, unfortunately, the test has been largely restricted to the evaluation of patients with chronic heart failure (CHF). [7][8][9][10] Although the American Thoracic Society guideline for the 6 MWT states that a "recent" (within a month) MI is an absolute contraindication for the test, 11) few data are available to support this contention. In fact, to the best of our knowledge, no previous study has looked at the safety, reliability, and repeatability of the 6 MWT in patients recovering from an acute MI.…”
mentioning
confidence: 99%
“…(28) Additionally, treated patients were categorised in the < 300m bracket in the 6 min walking test, this test is strongly prognostic of subsequent mortality and hospital admission in stable chronic HF (29,30) and in patients with advanced HF. (31,32) Improvement of >100m was demonstrated in treated patients, (improvement of >50 m has been reported as clinically very meaningful, (33) while decreases in walking distance were found in control patients. New York Heart Association (NYHA) index was shown to decrease from a mean of 2.9 in treated patients to 1.96 over six has progressed through pre-clinical studies, (20,21,34) and is currently waiting to start phase I clinical trials (NCT02305602).…”
Section: Acellular Materials Based Scaffoldsmentioning
confidence: 92%